Changes in biological activity in Budapest and the Budapest Agglomeration between 1990 and 2005 - Gábor, Péter; Jombach , Sándor; Ongjerth, Richárd (4D Journal of Landscape Architecture and Garden Art, 2007)
Our research was carried out as a supporting programme during the process of elaboration of the green network development plan of Budapest. Utilising two Landsat images taken in 1990 and 2005 we developed a GIS based analytical method of describing the changes of biological activity (BA) in Budapest and its agglomeration.
Keywords: biological activity; Budapest; remote sensing; green area coverage; space rocording; NDVI; agglomeration